Correlation between previous treatment with BRAF inhibitors and clinical response to pembrolizumab in patients with advanced melanoma. (4th March 2017) - Simeone, Ester; Grimaldi, Antonio Maria; Festino, Lucia; Giannarelli, Diana; Vanella, Vito; Palla, Marco; Curvietto, Marcello; Esposito, Assunta; Palmieri, Giuseppe; Mozzillo, Nicola; Ascierto, Paolo Antonio
ABSTRACT: The optimal sequencing of targeted treatment and immunotherapy in the treatment of advanced melanoma is a key question and prospective studies to address this are ongoing. Previous observations suggest that treating first with targeted therapy may select for more aggressive disease, meaning that patients may not gain full benefit from subsequent immunotherapy. In a single-center retrospective analysis, we investigated whether response to pembrolizumab was affected by previous BRAF inhibitor therapy. A total of 42 patients with metastatic cutaneous or mucosal melanoma who had received previous treatment with ipilimumab were treated with pembrolizumab as part of the Italian expanded access program. Sixteen of these patients had BRAF-mutated melanoma and had also been previously treated with a BRAF inhibitor (vemurafenib or dabrafenib), while 26 had BRAF wild-type melanoma (no previous BRAF inhibitor). Patients with BRAF-mutant melanoma who were previously treated with BRAF inhibitors had a significantly lower median progression-free survival (3 [2.3–3.7] versus not reached [2–8+] mo; p = 0.001) and disease control rate (18.6% versus 65.4%; p = 0.005) than patients with BRAF wild-type, while there was also a trend toward a lower response rate (assessed using immune-related response criteria) although this was not significantly different between groups (12.5% versus 36.4%; p = 0.16). These data are consistent with previous reports that BRAF inhibitor therapy may affect subsequent response to immunotherapy.